ORGANIZATIONAL CULTURE AS THE ARCHITECTURE OF THE SPACE OF INNOVATION IN TRANSFORMATION PROCESSES OF SOCIO-ECONOMIC SYSTEMS - STADNYK, Valentyna; JATSJUK, Natalja; GONCHARUK, Olena; YOKHNA, Vitaliy; GONCHARUK, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The problem of reviving the economy of Ukraine in the post-war period cannot be solved without the transformation of the management system. It should be subordinated to development tasks, and its methods and tools should ensure purposeful, systematic and effective innovative activity of all business entities. The goals of the article are to develop scientific and methodical approaches to managing the development of the architecture of organizational relations in the "principal-agent" economic partnership to solve the problems of forming an organizational culture adequate to the goals of transformational processes, which are the basis of innovative strategies for the development of socio-economic systems. The work argues that one of the ways to solve these problems can be the development of organizational culture, which in the conditions of the post-war transformation of the domestic economy should form the architecture of the innovation space. The author's definition of this definition is given and the main requirements for creating such a space are characterized. It is noted that in order to solve this task in the organizational environment, it is necessary to diagnose the problems that arise in the "principal-agent" relationship. The author's position is formulated that the formation of organizational culture of this type should be carried out using methodological approaches of behavioral theory. Its attributes and values should increase the level of trust between management and employees, reducing the risks of opportunistic behavior and increasing organizational effectiveness.
Keywords: post-war revival of the economy; behavioral theory; system transformations; "principal-agent" relations; innovation; innovative development